2020
DOI: 10.2147/rrn.s223472
|View full text |Cite
|
Sign up to set email alerts
|

<p>Individualizing Oral Feeding Assessment and Therapies in the Newborn</p>

Abstract: Oral feeding competency is a milestone most infants must achieve prior to discharge. It is a developmentally complex task that requires integration of multiple sensory inputs, central nervous system maturation, motor coordination, and respiratory stability. While ensuring safety during oral feeding is important to reduce morbidities, we must optimize developmental windows to expedite feeding maturation. Currently, many of the assessments and therapies related to oral feeding skills focus solely on nutritive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Results identified a wide range of flow rates (7.33mL/min-25.33mL/min) and variability of flow within each teat tested, confirming the study hypotheses that suggested this would be the case. Preterm and medically fragile infants present with immature oral feeding skills and often receive their first oral suck feed on the unit, developing and refining oral feeding competence alongside other skills in readiness for discharge home (Azuma and Maron 2020). Learning to bottle feed can be interrupted by variable flow rate of milk from a teat which subsequently influences timing and trigger of the swallow, thereby increasing risk of apnoeic episodes and aspiration (Chen, Wang, Chang & Chi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Results identified a wide range of flow rates (7.33mL/min-25.33mL/min) and variability of flow within each teat tested, confirming the study hypotheses that suggested this would be the case. Preterm and medically fragile infants present with immature oral feeding skills and often receive their first oral suck feed on the unit, developing and refining oral feeding competence alongside other skills in readiness for discharge home (Azuma and Maron 2020). Learning to bottle feed can be interrupted by variable flow rate of milk from a teat which subsequently influences timing and trigger of the swallow, thereby increasing risk of apnoeic episodes and aspiration (Chen, Wang, Chang & Chi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the neonatal period, this is thought to be regulated by bilateral brainstem neural networks in the pontine and medullary reticular formation, called the suck central pattern generator (CPG). The CPG is responsive to stimulation and can be trained using oral stimulation with pacifiers, nipples, breastfeeding, and olfactory, tactile, or thermal stimulation [ 13 , 17 , 18 , 19 ]. Sucking is reflexive in neonates and becomes more voluntary as the infant grows and learns to masticate [ 15 ].…”
Section: Understanding Oral Feeding and Feeding Problems In Preterm Infantsmentioning
confidence: 99%
“…Feeding problems are dynamic and continue to evolve as the infant grows, requiring an ongoing assessment, intervention, and re-evaluation to optimize management. Early diagnosis and treatment of feeding problems involve a holistic approach to the individual’s specific feeding difficulties in order to decrease potential long-term challenges [ 16 , 19 ]. Figure 3 suggests an algorithmic approach for managing feeding problems in the neonatal period continuing into childhood.…”
Section: Addressing Oral Feeding Issues Earlymentioning
confidence: 99%
See 1 more Smart Citation
“…The nfant SSB Sensor connects to the coupling and wirelessly transmits real-time data on nipple movement to a tablet via the nfant Mobile App. nFS addresses a significant limitation of other devices as the real-time feedback of sucking performance allows the healthcare team to see the immediate impact of an intervention to improve feeding ( 98 ). Following a feeding, waveforms of NNS and NS nipple movement are transmitted to the HIPAA protected nfant Cloud Database and the signals converted via custom algorithms, to identify key features and measures that describe sucking performance.…”
Section: Quantitative Measuresmentioning
confidence: 99%